Numerical Investigation on Ion Inertia Force in Low-Temperature Plasma Using Fluid Model Considering Ion Momentum Equation - Chen, Kuan-Lin; Tseng, Meng-Fan; Gu, Bi-Ren; Hung, Chieh-Tsan; Wu, Jong-Shinn (My University, 2016)
In this paper, we would like to numerically investigate the effect of ion inertia force in a typical argon gas discharge using fluid model considering the ion momentum equation, which becomes important under various operating conditions. The proposed self-consistent fluid model consists of the electron continuity equation with the drift-diffusion approximation, the ion continuity equation, the electron energy density equation, the ion momentum equation, and the Poisson equation for electric potential. We studied the plasma properties affected by the inertia force by comparing between the use of momentum equation and drift-diffusion approximation for ion momentum. The results show that the ion inertia force is significant under the low-pressure conditions (<100 mtorr) as expected, e.g., for plasma etching and radio frequency magnetron sputtering plasma. In addition, we also found when the pressure is higher than 100 mtorr, the inertia force becomes important (e.g., more than 15%) in the sheath region when the driving frequency is high enough (e.g., 60 MHz), e.g., for high-frequency plasma-enhanced chemical vapor deposition. Thus, inclusion of inertia force in the modeling of momentum equation becomes necessary under these operating conditions.
Keywords: Numerical analysis; plasma applications; pressure effects